GRAPH RAG UNTUK MEMAHAMI PERATURAN TENTANG PAJAK KENDARAAN BERMOTOR DI PROVINSI BANTEN [GRAPH RAG TO UNDERSTAND THE REGULATION ON MOTOR VEHICLE TAX IN BANTEN PROVINCE] - Prihartono, Agung; Priantoro, Akhmad Unggul (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
Local regulation documents (Perda) often have a complex structure and intricate language, making them difficult for the general public to understand. Large Language Models (LLM) offer the potential to simplify this information but carry the risk of generating inaccurate or